CDOs and the Financial Crisis: Credit Ratings and Fair Premia - Marcin Wojtowicz (Tinbergen Institute, 2011)
This paper uses the market-standard Gaussian copula model to show that fair spreads on CDO tranches are much higher than fair spreads on similarly-rated corporate bonds. It implies that credit ratings are not sufficient for pricing, which is surprising given their central role in structured finance markets. Tranche yield enhancement is attributed to a concentration of collateral bonds' risk premia in spreads of non-equity tranches. This illustrates limitations of the rating methodologies, which are solely based on estimates of real-world payoff prospects and thus do not capture risk premia. We also show that payoff prospects and credit quality of CDO tranches are characterized by low stability. If credit conditions deteriorate, then prices and ratings of CDO tranches are likely to fall substantially further than prices and ratings of corporate bonds. Default contagion exacerbates the pace and severity of changes for CDO tranches.
Keywords: C52; G01; G11; 330; Collateralized debt obligations; Credit ratings; Fair premia; Structured finance; Rating agencies; Asset-Backed Securities; Risikoprämie; Kreditrisiko; Bewertung; USA